Self-organization in semiconductors with drift instability under influence of modulated light. II. Light response to external field variations - Chupyra, S.M.; Horley, P.P.; Gorley, P.M. (Functional Materials, 2005)
The spectral dependence of photo-response for a finite size semiconductor under Gunn effect has been theoretically studied. А correlation has been established between the voltage variations across a sample and current and illumination time-harmonic variations. The problem of the light response frequency dispersion, in particular, in the voltage and current generation modes has been considered. The light response spectral dependences have been shown to be substantially different in voltage and current generation modes. For a semiconductor with n-GaAs parameters show that the above dependences for long and short samples are different in character. This fact is supposed to be caused by an area of spatially inhomogeneous distribution of volume charge appearing under illumination, that area contributing to different extent to the integral characteristic, depending on the sample length. Теоретически исследована спектральная зависимость фотоотклика полупроводника конечных размеров в условиях существования Ганн-эффекта. Обнаружена связь между изменениями напряжения на образце и вариациями тока и освещенности, изменяющихся во времени по гармоническому закону. Рассмотрен вопрос о частотной дисперсии фотоотклика, в частности, в режимах генератора напряжения и тока. Показано, что спектральные зависимости фотоотклика в режимах генератора напряжения и тока существенно отличаются друг от друга. Для полупроводника с параметрами n-GaAs показывают, что характер указанных зависимостей для длинных и коротких образцов различен. Высказано предположение, что последнее, вероятно, обусловлено возникновением при освещении области пространственно-неоднородного распределения объемного заряда, которая дает различный вклад в интегральную характеристику в зависимости от длины образца. Теоретично дослiджено спектральну залежнiсть фотовiдгуку напiвпровiдника кiнцевих розмiрiв в умовах iснування Ганн-ефекту. 3найдено зв'язок мiж варiацiями напруги на зразку та варiацiями струму та освiтлення, якi змiнюються з часом за гармонiйним законом. Розглянуто питання про частотну дисперсiю фотовiдгуку i, зокрема, у режимах генератора напруги та струму. Показано, що спектральнi залежностi фотовiдгуку у режимах генератора напруги та струму суттєво вiдрiзняються одна вiд iншої. Для напiвпровiдника з параметрами n-GaAs характер зазначених залежностей для довгих i коротких зразкiв є рiзним. Висловлено припущення, що останнє, напевно, обумовлено виникненням при освiтленнi областi просторово-неоднорiдного розподiлу об'ємного заряду, яка дає рiзний вклад в iнтегральну характеристику в залежностi вiд довжини зразка.